PENGARUH REPUTASI AUDITOR DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016 dan 2017) - Maria Widi Hapsari; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This study aims to empirically examine the relation between auditor reputation and auditor industry specialization and audit report lag to the manufacturing companies listed on Indonesia Stock Exchange in 2016-2017. This study uses secondary data from financial statements of manufacturing companies listed on Indonesia Stock Exchange in 2016-2017. The sampling method used is purposive sampling. The sample consists of 234 financial reports from 153 companies that listed in Indonesia Stock Exchange period 2016-2017. The analysis method that was used in this study was multiple regression analysis. Before being conducted by regression test, it was examined by using classical assumption test.The result of this study shows that both of the independent variables, reputation auditor and auditor industry specialization, have negatife significant influence to audit report lag.